Effect of Empagliflozin on Cardiovascular and Renal Outcomes in Patients With Heart Failure by Baseline Diabetes Status: Results From the EMPEROR-Reduced Trial. Issue 4 (26th January 2021) - Anker, Stefan D.; Butler, Javed; Filippatos, Gerasimos; Khan, Muhammad Shahzeb; Marx, Nikolaus; Lam, Carolyn S.P.; Schnaidt, Sven; Ofstad, Anne Pernille; Brueckmann, Martina; Jamal, Waheed; Bocchi, Edimar A.; Ponikowski, Piotr; et al.
Abstract : Background: Sodium-glucose cotransporter 2 inhibitors improve outcomes in patients with heart failure with reduced ejection fraction, but additional information is needed about whether glycemic status influences the magnitude of their benefits on heart failure and renal events. Methods: Patients with Class II–IV heart failure and a left ventricular ejection fraction ⩽40% were randomized to receive empagliflozin (10 mg daily) or placebo in addition to recommended therapy. We prespecified a comparison of the effect of empagliflozin in patients with and without diabetes. Results: Of the 3730 patients enrolled, 1856 (50%) had diabetes, 1268 (34%) had prediabetes (hemoglobin A1c [HbA1c] 5.7–6.4%), and 606 (16%) had normoglycemia (HbA1c <5.7%). The risks of the primary outcome (cardiovascular death or hospitalization for heart failure), total hospitalizations for heart failure, and adverse renal outcomes were higher in patients with diabetes, but were similar between patients with prediabetes and normoglycemia. Empagliflozin reduced the risk of the primary outcome in patients with and without diabetes (hazard ratio, 0.72 [95% CI, 0.60–0.87] and 0.78 [95% CI, 0.64–0.97], respectively, P -interaction=0.57). Patients with and without diabetes also did not differ with respect to the effect of empagliflozin on total hospitalizations for heart failure, on the decline in estimated glomerular filtration rate over time, and on the risk of serious adverse renal outcomes. Among these end points, the effects of the drug did not differ in patients with prediabetes or normoglycemia. When analyzed as a continuous variable, baseline HbA1c did not significantly modify the benefits of empagliflozin on the primary outcome ( P -interaction=0.40). Empagliflozin did not lower HbA1c in patients with prediabetes or normoglycemia and was not associated with increased risk of hypoglycemia. Conclusions: In EMPEROR-Reduced (Empagliflozin Outcome Trial in Patients With Chronic Heart Failure With Reduced Ejection Fraction), empagliflozin significantly improved cardiovascular and renal outcomes in patients with heart failure and a reduced ejection fraction, independent of baseline diabetes status and across the continuum of HbA1c. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03057977. Abstract : Supplemental Digital Content is available in the text.